Screening for autoantibodies in chronic hepatitis C patients has no effect on treatment initiation or outcome. Issue 4 (4th October 2012) - Mauss, S.; Berger, F.; Schober, A.; Moog, G.; Heyne, R.; John, C.; Pape, S.; Hueppe, D.; Pfeiffer‐Vornkahl, H.; Alshuth, U.
Summary Autoantibodies in hepatitis C virus–infected patients may indicate autoimmune hepatitis or other immune‐mediated diseases. This may impact safety and efficacy of interferon‐based therapy of chronic hepatitis C. We investigated the association between a positive test result for a variety of autoantibodies and the initiation and efficacy of therapy for chronic hepatitis C. We analysed an observational cohort of 24 306 patients for an association between autoantibodies and treatment outcome. 8241 patients were tested simultaneously for antinuclear antibodies (ANA), liver kidney microsomal antibodies (LKM), smooth muscle antibodies (SMA) and antimitochondrial antibodies (AMA). Matched‐pair analysis was performed matching one autoantibody‐positive patient to three controls. Control patients had negative tests for all four antibodies. Analyses were performed for patients with a single positive autoantibody test and for patients with multiple positive autoantibody tests. A positive test result for ANA, LKM, SMA or AMA did not affect the physician's decision to initiate therapy with pegylated interferon and ribavirin. In addition, a positive test for one or multiple autoantibodies did not adversely affect sustained virologic response. There was no difference in fibrosis stage or alanine transaminase at baseline or during therapy irrespective of antibody status. Thyroid dysfunction was more frequent in patients with positive LKM antibodies (P = 0.004). Initiation of therapy for chronic hepatitis C and outcome were not affected by the presence of ANA, LKM, SMA or AMA. Routine testing of these autoantibodies seems not warranted. Determination of autoantibodies should be guided by individualized clinical decisions.